Natural Transformation of Riemerella columbina and Its Determinants - Huang, Li; Liu, Mafeng; Zhu, Dekang; Xie, Li; Huang, Mi; Xiang, Chen; Biville, Francis; Jia, Renyong; Chen, Shun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; et al. (Frontiers in Microbiology, 2021)
In a previous study, it was shown that Riemerella anatipestifer, a member of Flavobacteriaceae, is naturally competent. However, whether natural competence is universal in Flavobacteriaceae remains unknown. In this study, it was shown for the first time that Riemerella columbina was naturally competent in the laboratory condition; however, Flavobacterium johnsoniae was not naturally competent under the same conditions. The competence of R. columbina was maintained throughout the growth phases, and the transformation frequency was highest during the logarithmic phase. A competition assay revealed that R. columbina preferentially took up its own genomic DNA over heterologous DNA. The natural transformation frequency of R. columbina was significantly increased in GCB medium without peptone or phosphate. Furthermore, natural transformation of R. columbina was inhibited by 0.5 mM EDTA, but could be restored by the addition of CaCl2, MgCl2, ZnCl2 and MnCl2, suggesting that these divalent cations promote the natural transformation of R. columbina. Overall, this study revealed that natural competence is not universal in Flavobacteriaceae members and triggering of competence differs from species to species.